2020
DOI: 10.1002/cncr.32702
|View full text |Cite
|
Sign up to set email alerts
|

Age dependence of modern clinical risk groups for localized prostate cancer—A population‐based study

Abstract: Background Optimal prostate cancer (PCa) screening strategies will focus on men likely to have potentially lethal disease. Age‐specific incidence rates (ASIRs) by modern clinical risk groups could inform risk stratification efforts for screening. Methods This cross‐sectional population study identified all men diagnosed with PCa in Norway from 2014 to 2017 (n = 20,356). Age, Gleason score (primary plus secondary), and clinical stage were extracted. Patients were assigned to clinical risk groups: low, favorable… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 38 publications
(92 reference statements)
5
22
1
Order By: Relevance
“…Determination of age of aggressive disease onset is thus highly relevant. Data from the CAP study shown here confirm prior findings of increasing risk of aggressive prostate cancer as men age [21][22][23][24] . However, the proportion of new prostate cancer diagnoses classified as aggressive in CAP is higher than some older studies that were limited to men with low PSA and normal digital rectal exam [25][26][27] , while modern population studies show similar or higher proportions with aggressive disease 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Determination of age of aggressive disease onset is thus highly relevant. Data from the CAP study shown here confirm prior findings of increasing risk of aggressive prostate cancer as men age [21][22][23][24] . However, the proportion of new prostate cancer diagnoses classified as aggressive in CAP is higher than some older studies that were limited to men with low PSA and normal digital rectal exam [25][26][27] , while modern population studies show similar or higher proportions with aggressive disease 21 .…”
Section: Discussionsupporting
confidence: 87%
“…Clinically meaningful risk stratification is illustrated by the estimated cumulative incidence curves in Figure 1. This effect is particularly pronounced for clinically significant disease because of the increased proportion of clinically significant cases observed at older ages 2,20,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Age is a critical consideration in prostate cancer decision-making 29 , especially as medical co-morbidities and competing risk of death increase with aging 30 . At the same time, prostate cancer incidence rises exponentially with age and is typically more aggressive when diagnosed at an older age 31,32 .…”
Section: Discussionmentioning
confidence: 99%